11y-16=7y

Simple and best practice solution for 11y-16=7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11y-16=7y equation:


Simplifying
11y + -16 = 7y

Reorder the terms:
-16 + 11y = 7y

Solving
-16 + 11y = 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
-16 + 11y + -7y = 7y + -7y

Combine like terms: 11y + -7y = 4y
-16 + 4y = 7y + -7y

Combine like terms: 7y + -7y = 0
-16 + 4y = 0

Add '16' to each side of the equation.
-16 + 16 + 4y = 0 + 16

Combine like terms: -16 + 16 = 0
0 + 4y = 0 + 16
4y = 0 + 16

Combine like terms: 0 + 16 = 16
4y = 16

Divide each side by '4'.
y = 4

Simplifying
y = 4

See similar equations:

| 3h/5-18=713/40 | | 2x-3+4x-7= | | 207-x=23 | | 6n+3=10 | | 12m-5=-2(6m+3) | | 4(f+h)-8p=3k | | 259=-v+182 | | 8w^2-14w+5=0 | | 49-121+12+4Y=-3Y+2(3) | | 8y-6y-9=23.24 | | 141=-3x+6(6x-4) | | -5-8f-10=-8f-5 | | -3=4w-7 | | -13=3+2m-6 | | -44=-4x+8 | | 1/5(10t-15)=2t | | 4+5w=-26 | | 3=1y+7 | | 3(a+5)-12=2(a-3) | | 9y+3=13y-8 | | (10x-15)/5=2x | | 4x=5+6x | | 12-2x+5x=4 | | 6n+3=4 | | 14=6+u/2 | | (10x-15)/5=2t | | -5-8f-10=8f+5 | | -k-5k=12 | | 450=0.80(d-100) | | 15v^2-70v+49=0 | | 45-9/9x2 | | -9/13z=0 |

Equations solver categories